IN VIVO ACUTE TOXICITY, ANTIBACTERIAL, ANTIAQUATIC FUNGAL, ANTHELMINTHIC ACTIVITY OF LACTOBACILLUS PLANTARUM KP894100 AND LACTOBACILLUS ACIDOPHILUS KP942831 - Bharti, Vandana; Mehta, Archana; Jain, Neha; Singh, Siddhartha; Ahirwal, Laxmi (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: This study observed the antibacterial, antifungal (aquatic and pathogenic fungi), and anthelmintic properties of Lactobacillus plantarum (LP) KP894100 and Lactobacillus acidophilus (LC) KP942831, isolated from a dairy product. Methods: Lactic acid bacteria traditionally used to improve human health. For in vitro antibacterial, antifungal, and antihelminthic studies of intracellular cell-free extract (ICFE) from LP and LC were produced separately by using filtration methods. ICFE was freeze-dried then resuspended in citrate phosphate buffer. This ICFE is further used for the antimicrobial and anthelmintic assay. In the antimicrobial assay, ICFE were tested against pathogenic bacteria, i.e., Bacillus subtilis, Escherichia coli, Enterococcus faecalis, Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas stutzeri, Pseudomonas aeruginosa, and aquatic fungal species including: Aspergillus clavatus, Pythium aphanidermatum Saprolegnia parasitica, Candida albicans, Aspergillus fumigatus, Fusarium oxysporum, Alternaria alternata, Curvularia sp., Mucor sp., Rhizopus stolonifer, Aspergillus niger, and Penicillium chrysogenum. In the anthelmintic assay, young stages of Pheretima posthuma (Indian earthworms) were used. For the analysis of acute toxicity assay different graded doses (100, 250, 500, 1000 mg/kg bw) of ICFE of LP and LC was administered in Wistar albino rats, respectively, and the control group received distilled water. Result: The ICFE of both Lactobacillus strains showing strong antibacterial and weak antifungal activity against aquatic fungi except, S. parasitica, and C. albicans. The ICFE shows 100% paralysis and killing efficacy against P. posthuma in 48-72 hrs. In the acute toxicity test, LP and LC did not produce any toxic signs or death at the maximum concentration 1000 mg/kg bw. Conclusion: ICFE of LP and LC possess anthelmintic activity against P. posthuma with only strong antibacterial activity. Both the lactobacillus strains have strong antibacterial activity and have potential activity against P. posthuma helminthes. Keywords: Antimicrobial, Antifungal, Aquatic fungi, Anthelmintic activity, Pheretima posthuma.